Evaluation of Self Contentment with Dental Appearance and Preference to Treatment to Improve Esthetics - Singh, T; Ghimire, T R (Journal of Nepalese Prosthodontic Society, 2020)
Introduction: Oral health not only comprises of mere absence of oral disease and dysfunction but also includes dental appearance for overall facial beauty as it has influence on person’s self confidence and social life. Dental aesthetic comprises of tooth color, shape, alignment and position of the teeth in the dental arches. For the rewarding outcome of the treatment, clinician need to understand the root of dissatisfaction with present aesthetic and desired treatment to enhance the aesthetic that will assist in development of treatment plan.Materials and Methods: Pre-tested structured questionnaire was used in 349 subjects from previous studies with slight modification for data collection. The questionnaire was divided into three parts, first part recorded the demographic data, second part consisted of the patients’ view regarding satisfaction of the dental appearance and third part consist of the Likert scale where participants will rate the satisfaction level regarding their general appearance.Results: A relationship between gender (P